Monumen Perjuangan Angsana Sari Desa Titab, Kecamatan Busungbiu, Buleleng (Latar Belakang Dan Strategi Pemanfaatannya Sebagai Sumber Belajar Sejarah Di SMA) - Hajaro, Nugraha; I Wayan Putra Yasa; I Wayan Pardi (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
ABSTRACT This research examines the Angsana Sari Struggle Monument in Titab Village, Buleleng, as a symbol of local struggle. The aim of the research is to explore the background to the erection of the monument, the character values ​​contained, and its use as a history learning resource in high school. The method used is descriptive qualitative. Data was obtained by conducting observations, interviews and document studies. The results of the research show that the monument was erected to commemorate the incident of the NICA army's ambush of young fighters. The character values ​​contained in the monument include religion, hard work, love of the country, democracy, national spirit, love of peace, respect for achievement, social care, responsibility and friendship. The use of monuments as a historical learning resource applies the Problem Based Learning (PBL) model in accordance with the curriculum. This research contributes to the preservation of historical values ​​and character for the younger generation. Keywords: Young generation, Angsana Sari Struggle Monument, character values, learning resources